Fermented Foods: Are They Tasty Medicines for Helicobacter pylori Associated Peptic Ulcer and Gastric Cancer? - Nair, Mydhily R. B.; Chouhan, Deepak; Sen Gupta, Sourav; Chattopadhyay, Santanu (Frontiers in Microbiology, 2016)
More than a million people die every year due to gastric cancer and peptic ulcer. Helicobacter pylori infection in stomach is the most important reason for these diseases. Interestingly, only 10-20% of the H. pylori infected individuals suffer from these gastric diseases and rest of the infected individuals remain asymptomatic. The genotypes of H. pylori, host genetic background, lifestyle including smoking and diet may determine clinical outcomes. People from different geographical regions have different food habits, which also include several unique fermented products of plant and animal origins. When consumed raw, the fermented foods bring in fresh inocula of microbes to gastrointestinal tract and several strains of these microbes, like Lactobacillus and Saccharomyces are known probiotics. In vitro and in vivo experiments as well as clinical trials suggest that several probiotics have anti-H. pylori effects. Here we discuss the possibility of using natural probiotics present in traditional fermented food and beverages to obtain protection against H. pylori induced gastric diseases.